Problematics of Science Learning With Limited Educators at Sentul Community Learning Center Kuala Lumpur - Anggun Rahmayanti; Arinta Rezty Wijayaningputri; Innany Mukhlishina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: In the context of science learning, the readiness of teaching staff greatly influences learning because the difficulties experienced by teachers are a trigger for learning failure in students and give rise to the view that science is a difficult subject. Aim: The aim of this research is to analyze the problems of science learning within the limited teachers in the Sentul Community Learning Center Kuala Lumpur. The Sentul Community Learning Center is a non-formal school for Indonesian immigrant children who do not have the opportunity to attend formal school in Kuala Lumpur. Method: This research uses a qualitative approach, and the type of research is descriptive research. The data collection methods used were interviews, observation, and documentation. Results and Dıscussion: In implementing science learning at the Sentul Community Learning Center, there are many limitations, especially in terms of teachers. Science learning is taught to students in grades three to six at one time because the Sentul community learning center lacks teachers and there are no adequate facilities to support science learning. Conclusion: Even though science learning at the Sentul community learning center is not yet effective and efficient, considering all the limitations of teaching staff as well as media and infrastructure for science learning, the implementation of learning at the Sentul community learning center is one form of effort made so that students receive education equivalent to formal schools.